Pandemic Poetry and Interventions in World on the Brinks: An Anthology of Covid-19 Pandemic: A Postcolonial Reading - Afolayan, Kayode Niyi (SCHOLARS: Journal of Arts & Humanities, 2024)
Unarguably, the Covid-19 pandemic has remained a global experience that has altered aspects of life in all spaces. As global citizens adjust to the “new normal” protocols of living, most engagements of critics with literary works on the pandemic have found ecocriticism as a veritable theoretical tool in harnessing mirrored ordeals of the pandemic. However, this paper adopts the postcolonial theory to engage with the pandemic verses in Ikechukwu Otuu Egbuta and Nnenna Vivien Chukwu’s World on the Brinks: An Anthology of Covid-19 Pandemic. The paper contextualises the studied text within the evolution of the anthology genre in modern Nigerian poetry and harnesses the critical perspectives on the expediency of poetry as intervening tool in crisis situations. After its rigorous analyses of the selected poems which slant the impacts of the pandemic into universal and domestic domains, the conclusion of the paper harps on the urgency to re-awake humane values for a better universe. However, for Third World nations, where the pandemic exposed vulnerability and dystopias, the urgent call remains the recovery of leadership and institutions which are in the throes of total collapse.